1996
DOI: 10.2307/1243791
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Wheat Variety Selection in Kansas, 1974 to 1993

Abstract: In 1993, over one-third of Kansas wheat acres were seeded to varieties with milling and baking qualities ranked “less desirable,” stimulating interest in the determinants of wheat variety selection. Regression analysis is used to quantify the relationship between planted varieties and wheat characteristics relating to production and end-use qualities. Results indicate that Kansas wheat producers consider end-use qualities, production characteristics, relative yields, yield stability, and past production decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 9 publications
2
47
0
1
Order By: Relevance
“…wheat producers in Kansas take into account end-use quality in varietal selection decisions, but economic considerations lead many farmers to plant higher-yielding varieties, some of which are characterized by low milling and baking qualities'' (p. 209). Barkley and Porter (1996) also found that yield stability was a significant determinant of variety selection decisions, as discussed in Porter and Barkley (1995).…”
Section: Literature Reviewmentioning
confidence: 79%
See 4 more Smart Citations
“…wheat producers in Kansas take into account end-use quality in varietal selection decisions, but economic considerations lead many farmers to plant higher-yielding varieties, some of which are characterized by low milling and baking qualities'' (p. 209). Barkley and Porter (1996) also found that yield stability was a significant determinant of variety selection decisions, as discussed in Porter and Barkley (1995).…”
Section: Literature Reviewmentioning
confidence: 79%
“…The authors concluded that, ''the major implication of this result is the need to recognize the importance of competing hypotheses in the applied study of technology adoption'' (p. 544). Barkley and Porter (1996) analyzed Kansas wheat producer variety selection decisions for the period 1974-1993, and found that variety choice was statistically related to production characteristics such as disease resistance and end-use qualities. They concluded, ''.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations